Efektivitas Penggunaan Modul Pembelajaran Inovatif Berdasarkan Kurikulum 2013 Terhadap Peningkatan Hasil Belajar Siswa - Dewi Natalia Marpaung; Jesi Jecsen Pongkendek; Lamtiar Ferawaty Siregar (Faculty of Teacher Training and Education, Musamus University, 2020)
This study aims to determine the effectiveness of innovative learning modules based on curriculum 2013 on improving student learning outcomes. The method of this research was purpose sampling which was conducted at the Santo Thomast-1 Medan Private High School which consisted of 30 students in the control and experiment class. The initial stages of this research were carried out by giving a pretest for both classes, then learning was carried out using innovative textbooks in the experimental class and chemistry books used in the target school for the control class. Based on the value of the analysis conducted posttest in the control class is 75.75 while in the experimental class is 87.5 the magnitude of the increase in the posttest is 54.25% in the experimental class while in the control class is only about 43.5%, it can be concluded that the use of innovative learning modules based on curriculum 2013 effective to improve student learning outcomes.